MiRNA‐940 reduction contributes to human Tetralogy of Fallot development. Issue 9 (1st June 2014) - Liang, Dandan; Xu, Xinran; Deng, Fangfei; Feng, Jing; Zhang, Hong; Liu, Ying; Zhang, Yangyang; Pan, Lei; Liu, Yi; Zhang, Dasheng; Li, Jun; Liang, Xingqun; et al.
Abstract Tetralogy of Fallot (TOF) is a complex congenital heart defect and the microRNAs regulation in TOF development is largely unknown. Herein, we explored the role of miRNAs in TOF. Among 75 dysregulated miRNAs identified from human heart tissues, miRNA‐940 was the most down‐regulated one. Interestingly, miRNA‐940 was most highly expressed in normal human right ventricular out‐flow tract comparing to other heart chambers. As TOF is caused by altered proliferation, migration and/or differentiation of the progenitor cells of the secondary heart field, we isolated Sca‐1+ human cardiomyocyte progenitor cells (hCMPC) for miRNA‐940 function analysis. miRNA‐940 reduction significantly promoted hCMPCs proliferation and inhibited hCMPCs migration. We found that JARID2 is an endogenous target regulated by miRNA‐940. Functional analyses showed that JARID2 also affected hCMPCs proliferation and migration. Thus, decreased miRNA‐940 affects the proliferation and migration of the progenitor cells of the secondary heart field by targeting JARID2 and potentially leads to TOF development.